Evaluating the effectiveness of a consumer financial compliance training program - Jenkins, Wanda L. (University of Wisconsin--Stout, 2019)
The effectiveness Company XYZ compliance training program had never been assessed even though the company has had a compliance training program for the past five years. This study examined how effective the compliance training at Company XYZ was based on Kirkpatrick's four levels of training evaluation. Research was conducted via reactionary data from current employees as well as the compliance department. It also examined compliance training quiz data using a control group that was compared to existing employee quiz data. Recommendations included restructuring of the compliance trainings to include more role relevant applications such as scenario-based training and restructuring of compliance quizzes to reflect the objectives of the compliance trainings.
Keywords: Compliance; Employees